Ion Chromatographic Estimation of Arsenite and Arsenate at Trace Level. Issue 4 (2011) - Chavan, Chetan; Bhate, Vijayanand; Thaker, Chanakya; Khandkar, Aditi
Abstract : Present method shows simple and specific determination of traces of inorganic arsenic in water. This method enables simultaneous determination of arsenite by electrochemical detection and arsenate by suppressed conductivity detection. The applicability of this method was illustrated by determining the inorganic arsenite and arsenate content from bore-well water and river water samples without any special pretreatment. The present method for direct determination of arsenite and arsenate shows good sensitivity, selectivity, precision and accuracy. Detection limits determined using this procedure was found to be 2.0 μg/L for arsenite and 30.0 μg/L for Arsenate. The simplicity, ease of use, low detection limit and low running cost of this method makes it appealing for increasing capability of testing in the lab.